Silk fibroin composite gel and preparation method thereof
Through dynamic Schiff alkali bond cross-linking and disulfide bond strengthening, the preparation method of silk fibroprotein composite gels is solved, and the problems of irreversibility, low strength and single function of traditional silk fibroprotein gels are achieved, injectability, shapeability and versatility are achieved, and soft tissue repair and medical beauty filling are suitable for soft tissue repair.
Patent Information
- Application Number
- CN202510534826.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-08-19
- Estimated Expiration
- 2045-04-27
AI Technical Summary
The existing silk fibroin gels are irreversible after cross-linking, have low strength and single functions, making them difficult to match complex tissue profiles, are prone to collapse after filling, and lack the functions of promoting tissue regeneration, anti-inflammatory or antibacterial.
The dynamic Schiff alkali bond cross-linking is performed by aminating silk fibroin and oxidized sodium alginate, and the temperature-sensitive components and active ingredients are added to form a temperature-sensitive dual network, and the disulfide bond is introduced for cross-linking and strengthening, and a silk fibroin complex gel is prepared.
It realizes the reversible shaping, rapid gelation and versatility of the gel, can match complex tissue forms, and has self-healing capabilities, providing multiple functions such as mechanical filling, growth promotion, and antibacterial.
Smart Images

Figure CN120501932A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tissue filling materials, and in particular to a silk fibroin composite gel and a preparation method thereof. Background Art
[0002] Silk fibroin is a high-molecular-weight protein that primarily contains 18 amino acids. It possesses excellent mechanical properties, biocompatibility, and biodegradability, and has promising application prospects in the fields of biomaterials and tissue engineering. Silk fibroin can be used to prepare tissue filler materials. Through minimally invasive local injection therapy, filler materials with skin tissue repair capabilities are injected into local soft tissues with structural laxity to improve skin laxity and repair the tissue, thereby restoring the normal function and appearance of the tissue. Although traditional injectable filler materials (such as hyaluronic acid and polylactic acid microspheres) are widely used in clinical practice, they suffer from problems such as insufficient mechanical properties, uncontrollable degradation, and chemical cross-linking agents that easily destroy active ingredients, leading to loss of biological activity. Although silk fibroin gels are also used as filling materials in the prior art, they still have the following defects: (1) irreversible cross-linking and shaping defects, most of which rely on chemical covalent bonds (such as glutaraldehyde cross-linking), and cannot be adjusted by body temperature or mechanical force after injection, making it difficult to match complex tissue contours (such as nasolabial grooves and tear grooves); (2) single network gels, which have low strength and are prone to collapse after filling, requiring repeated injections; (3) single function, existing silk fibroin gels generally only provide mechanical filling, lack tissue regeneration, anti-inflammatory or antibacterial functions, and are prone to infection or fibrosis after surgery. Based on this, the present application proposes a silk fibroin composite gel and a preparation method thereof. Summary of the Invention
[0003] The main purpose of this application is to provide a silk fibroin composite gel and a preparation method thereof, aiming to solve the technical problems of the existing silk fibroin composite gel being irreversible after cross-linking, having low strength and single function.
[0004] To achieve the above objectives, the present application proposes a method for preparing a silk fibroin composite gel, comprising the following steps:
[0005] preparing silk fibroin and performing amino modification on it to obtain amino-modified silk fibroin;
[0006] The amino-modified silk fibroin and oxidized sodium alginate are dynamically cross-linked via Schiff base bonds using an enzyme-catalyzed cross-linking process to obtain a dynamic cross-linked network solution;
[0007] Adding a temperature-sensitive component to the dynamic cross-linked network solution and mixing them to obtain a temperature-responsive temperature-sensitive-dynamic double network pregel solution;
[0008] loading active ingredients into the thermosensitive-dynamic double network pregel solution to obtain a composite gel solution;
[0009] After incubating the composite gel solution, a primary gel is obtained;
[0010] After disulfide bonds are introduced into the primary gel, cross-linking strengthening and sterilization are performed to obtain a silk fibroin composite gel.
[0011] Optionally, the step of preparing silk fibroin and performing amino modification on it to obtain amino-modified silk fibroin comprises:
[0012] Dissolve silk fibroin in lithium bromide solution, stir and dissolve at 60-65°C for 1-2 hours, and then dialysis and purification, and concentrate to a mass fraction of 6%-8% to obtain a silk fibroin solution;
[0013] 1,2-ethylenediamine is added to the silk fibroin solution, and then an EDC / NHS activator is added, and the pH is adjusted to 6.3-6.7. After reacting for 22 hours to 26 hours, the solution is dialyzed and freeze-dried to obtain amino-modified silk fibroin.
[0014] Optionally, the step of dynamically cross-linking the amino-modified silk fibroin and oxidized sodium alginate via Schiff base bonds using an enzyme-catalyzed cross-linking process to obtain a dynamic cross-linked network solution comprises:
[0015] The amino-modified silk fibroin and oxidized sodium alginate are dissolved in a PBS buffer solution at 4° C. to 10° C., and horseradish peroxidase and hydrogen peroxide are added thereto, and the mixture is reacted for 20 min to 30 min to form a Schiff base cross-linking system, thereby obtaining a dynamic cross-linking network solution.
[0016] The mass fraction of the amino-modified silk fibroin in the dynamic cross-linked network solution is 4wt%-6wt%; the oxidation degree of the oxidized sodium alginate is 20%-30%, and the mass fraction of the oxidized sodium alginate in the dynamic cross-linked network solution is 3wt%-5wt%.
[0017] Optionally, the temperature-sensitive component includes poloxamer F127 and poly (N-isopropylacrylamide) microgel.
[0018] Optionally, the step of loading the active ingredient into the thermosensitive-dynamic double network pre-gel solution to obtain a composite gel solution comprises:
[0019] Ultrasonic dispersion of active ingredients in the thermosensitive-dynamic double network pre-gel solution to obtain a composite gel solution;
[0020] The active ingredients include core-shell microspheres encapsulating growth factors and anti-inflammatory factors, antimicrobial peptides anchored by graphene oxide nanosheets, and superoxide dismutase mimics.
[0021] Optionally, the core-shell microspheres are prepared by the following steps:
[0022] Dissolve silk fibroin in water, add vascular endothelial growth factor freeze-dried powder, and vortex mix for 4-6 minutes to obtain the inner phase solution;
[0023] Dissolve polycaprolactone in chloroform, stir in a water bath at 37-42°C for 25-35 minutes, then add interleukin-10 freeze-dried powder, and disperse by ultrasonication to obtain an external phase solution;
[0024] The inner phase solution and the outer phase solution were added dropwise to a polyvinyl alcohol aqueous solution at a rotation speed of 450-550 rpm by a coaxial emulsification-solvent evaporation method to form a W / O / W double emulsion, which was then solidified and centrifuged to obtain the core-shell microspheres.
[0025] Optionally, the graphene oxide nanosheet-anchored antimicrobial peptide is prepared by the following steps, including:
[0026] Graphene oxide powder was added to PBS buffer and ultrasonically treated to obtain a graphene oxide dispersion.
[0027] The antimicrobial peptide LL-37 was dissolved in PBS buffer, and then added dropwise to the graphene oxide dispersion. After stirring for 10 hours to 14 hours, the mixture was centrifuged at a rate of 11,000 rpm to 13,000 rpm for 15 minutes to 25 minutes. After washing, the graphene oxide nanosheet-anchored antimicrobial peptide was obtained.
[0028] Optionally, the superoxide dismutase mimetic is a manganese-based metal-organic framework, which has a porous structure formed by manganese ions and organic ligands and is grafted into the thermosensitive-dynamic double network pregel solution through covalent bonds.
[0029] Optionally, after introducing disulfide bonds into the primary gel, the steps of performing cross-linking strengthening and sterilization to obtain a silk fibroin composite gel include:
[0030] The primary gel is immersed in a PBS buffer containing cystamine, the pH is adjusted to 7.0-7.5, cross-linked at 35-40° C. for 2 h to 4 h to form a dynamic disulfide bond network, and then sterilized with γ rays at a dose of 15 kGy-25 kGy to obtain a silk fibroin composite gel.
[0031] The present application also proposes a silk fibroin composite gel, which is obtained by the above-mentioned preparation method of the silk fibroin composite gel.
[0032] This application has at least the following beneficial effects:
[0033] The present application modifies silk fibroin by amino modification to make it contain amino groups, and then uses the amino-modified silk fibroin and oxidized sodium alginate (containing aldehyde groups) to cross-link through Schiff base bonds (dynamic covalent bonds), and introduces thermosensitive components to form a temperature-responsive thermosensitive-dynamic double network, so that the composite gel has the performance of thermosensitive rapid gelation; and then by introducing active ingredients, the composite gel can not only provide mechanical filling, but also has multiple functions such as growth promotion and antibacterial. Since the Schiff base bond is highly dynamic but has low strength, the present application performs cross-linking strengthening after the introduction of disulfide bonds to ensure the mechanical strength of the composite gel and avoid structural collapse after injection. Before injection (at low temperature), the dynamic bond (Schiff base bond) of the composite gel of the present application is in a weakly cross-linked state to maintain fluidity. After injection into the body, the dynamic bond recombination is triggered by body temperature (37°C), and it can quickly solidify to form a gel, maintaining injectability and improving mechanical strength through disulfide bond post-crosslinking after implantation. After injection, it can be reshaped to match complex tissue morphology and has strong self-repair ability. Therefore, this application systematically solves the problems of traditional injectable gels such as irreversibility, difficulty in matching complex tissue contours, single function, and easy collapse after filling through thermosensitive-dynamic dual network design, introduction of active ingredients and disulfide bond-enhanced cross-linking, thereby realizing the integration of "injection-gelation-shaping". BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0035] Figure 1 This is a flow chart of the preparation method of the silk fibroin composite gel described in the examples of this application;
[0036] Figure 2 This is a performance test result diagram of the silk fibroin composite gel described in the examples of this application.
[0037] The realization of the objectives, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the embodiments described are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.
[0039] In view of the technical problems existing in the prior art, the embodiments of the present application provide a method for preparing a silk fibroin composite gel, such as Figure 1 As shown, the following steps are included:
[0040] S10, preparing silk fibroin and performing amino modification on the silk fibroin to obtain amino-modified silk fibroin.
[0041] In a specific implementation process, the silk fibroin fiber is dissolved in a lithium bromide solution, stirred and dissolved at 60-65°C for 1-2 hours, and then dialyzed and purified and concentrated to a mass fraction of 6%-8% to obtain a silk fibroin solution;
[0042] 1,2-ethylenediamine is added to the silk fibroin solution, and then an EDC / NHS activator is added, and the pH is adjusted to 6.3-6.7. After reacting for 22 hours to 26 hours, the solution is dialyzed and freeze-dried to obtain amino-modified silk fibroin.
[0043] This application modifies silk fibroin by amino modification so that it carries amino (-NH2) groups, thereby increasing its reactivity with aldehyde-containing oxidized sodium alginate. This modification improves the hydrophilicity of silk fibroin in aqueous solution and provides stronger reaction sites for subsequent cross-linking reactions, making it more active.
[0044] S20, using an enzyme-catalyzed crosslinking process to dynamically crosslink the amino-modified silk fibroin and oxidized sodium alginate via Schiff base bonds to obtain a dynamic crosslinked network solution.
[0045] In a specific implementation process, the amino-modified silk fibroin and oxidized sodium alginate are dissolved in a PBS buffer solution at 4°C-10°C, and then horseradish peroxidase and hydrogen peroxide are added. After reacting for 20min-30min, a Schiff base cross-linking system is formed to obtain a dynamic cross-linking network solution;
[0046] The mass fraction of the amino-modified silk fibroin in the dynamic cross-linked network solution is 4wt%-6wt%; the oxidation degree of the oxidized sodium alginate is 20%-30%, and the mass fraction of the oxidized sodium alginate in the dynamic cross-linked network solution is 3wt%-5wt%.
[0047] Specifically, the preparation method of oxidized sodium alginate includes: dissolving sodium alginate in a buffer solution with a pH of 4.0-4.5, adding sodium periodate, with a molar ratio of sodium alginate to sodium periodate of 1:(0.8-1.0), and reacting in the dark for 6h-8h.
[0048] This application uses amino-modified silk protein (containing amino groups) and oxidized sodium alginate (containing aldehyde groups) to cross-link through Schiff base bonds (dynamic covalent bonds), and uses horseradish peroxidase and hydrogen peroxide to catalyze the reaction to form a reversible dynamic network. There is no chemical cross-linking agent involved. Horseradish peroxidase is a natural enzyme with no residual risk. The Schiff base bond is highly reversible and supports shaping after injection, avoiding the problem that the gel formed by traditional chemical cross-linking (such as covalent bonds) cannot be delivered through a syringe due to irreversibility.
[0049] S30, adding a temperature-sensitive component to the dynamic cross-linking network solution and mixing to obtain a temperature-responsive temperature-sensitive-dynamic double network pregel solution.
[0050] In a specific implementation process, the steps for preparing the poly (N-isopropylacrylamide) microgel include:
[0051] N-isopropylacrylamide monomer, N,N-methylenebisacrylamide and ammonium persulfate are dissolved in water and reacted at 55°C-65°C for 3.5h-4.5h under nitrogen atmosphere to obtain poly (N-isopropylacrylamide) (PNIPAM) microgel; the particle size of the PNIPAM microgel is 50nm-100nm.
[0052] Specifically, Pluronic F127 is a triblock copolymer (PEO-PPO-PEO) whose micelles dissolve at low temperatures (<15°C). When the temperature rises to body temperature (37°C), the hydrophobic PPO segments aggregate to form a micellar network, causing the solution viscosity to rise sharply, achieving a phase transition from liquid to gel. The lower critical solution temperature of PNIPAM microgel is about 32°C. When the temperature exceeds the lower critical solution temperature, its molecular chains change from hydrophilic to hydrophobic, undergoing phase contraction and forming physical cross-linking points. Embedding PNIPAM microgel in the micellar network of Pluronic F127 can further enhance the gel strength and has temperature-responsive reversibility, supporting local shaping after injection. Through the synergistic effect of Pluronic F127 and PNIPAM microgel, the silk fibroin composite gel can have rapid temperature-sensitive gelation, high mechanical strength and reversible plasticity, thereby adapting to complex filling needs.
[0053] S40, ultrasonically dispersing the active ingredient in the thermosensitive-dynamic double network pre-gel solution to obtain a composite gel solution.
[0054] Specifically, the active ingredients include core-shell microspheres encapsulating growth factors and anti-inflammatory factors, antimicrobial peptides anchored by graphene oxide nanosheets, and superoxide dismutase mimics.
[0055] The steps for preparing the core-shell microspheres include:
[0056] Dissolve silk fibroin in water, add vascular endothelial growth factor freeze-dried powder, and vortex mix for 4-6 minutes to obtain the inner phase solution;
[0057] Dissolve polycaprolactone in chloroform, stir in a water bath at 37-42°C for 25-35 minutes, then add interleukin-10 freeze-dried powder, and disperse by ultrasonication to obtain an external phase solution;
[0058] The inner phase solution and the outer phase solution were added dropwise to a polyvinyl alcohol aqueous solution at a rotation speed of 450-550 rpm by a coaxial emulsification-solvent evaporation method to form a W / O / W double emulsion, which was then solidified and centrifuged to obtain the core-shell microspheres.
[0059] The present application introduces the active ingredients vascular endothelial growth factor (VEGF) and interleukin-10 (IL-10), uses core-shell microspheres as carriers, and wraps VEGF with silk fibroin. Silk fibroin, as a natural polymer material, can provide excellent biocompatibility and degradability, avoiding the inflammatory response that may be caused by artificial synthetic materials. VEGF is a water-soluble growth factor. The silk fibroin aqueous solution forms a hydrophilic core layer, which wraps VEGF through hydrogen bonds and electrostatic effects to prevent its inactivation. At the same time, the β-pleated structure of silk fibroin can form a dense network, delaying the diffusion of VEGF and achieving sustained release of VEGF. Polycaprolactone, as a hydrophobic material, is dissolved in chloroform to form a continuous phase, which wraps the inner phase droplets to form a physical barrier. Since IL-10 is easily degraded by proteases, the polycaprolactone shell can block the external enzyme environment and maintain the activity of IL-10. This application uses the hydrophilicity of silk fibroin and the hydrophobicity of polycaprolactone, and precisely designs the structure of the core-shell microspheres through coaxial emulsification and stratification, thereby achieving the regulation of the release sequence of VEGF and IL-10 (VEGF sustained release + IL-10 rapid release), which not only ensures the dual effects of growth promotion and anti-inflammatory, but also makes the growth promotion and anti-inflammatory orderly connected to avoid functional antagonism.
[0060] The steps for preparing the graphene oxide nanosheet-anchored antimicrobial peptide include:
[0061] Graphene oxide powder was added to PBS buffer and ultrasonically treated to obtain a graphene oxide dispersion.
[0062] The antimicrobial peptide LL-37 was dissolved in PBS buffer, and then added dropwise to the graphene oxide dispersion. After stirring for 10 hours to 14 hours, the mixture was centrifuged at a rate of 11,000 rpm to 13,000 rpm for 15 minutes to 25 minutes. After washing, the graphene oxide nanosheet-anchored antimicrobial peptide was obtained.
[0063] Specifically, the superoxide dismutase mimetic is a manganese-based metal-organic framework (Mn-MOF), which has a porous structure formed by manganese ions and organic ligands and is covalently grafted into the thermosensitive-dynamic dual-network pregel solution. Mn-MOF can mimic the catalytic function of natural SOD and possesses antioxidant capacity to scavenge free radicals, with an in vitro superoxide radical scavenging rate of ≥85%. Covalently linking the Mn-MOF to silk fibroin allows for uniform dispersion within the gel while retaining its antioxidant activity.
[0064] This application uses graphene oxide as a carrier to anchor the antimicrobial peptide LL-37 to form an antibacterial complex GO / LL-37 to inhibit bacterial infection. Since bacterial infection can induce local reactive oxygen species (ROS) outbreaks, Mn-MOF can neutralize ROS and protect tissues from oxidative damage. At the same time, GO / LL-37 inhibits bacterial proliferation, forming a dual protection, blocking the vicious cycle of "infection-inflammation-oxidative stress", and jointly exerting antibacterial and antioxidant functions.
[0065] S50, incubating the composite gel solution to obtain a primary gel.
[0066] After the composite gel solution is injected into a mold, it is incubated at 35° C. to 40° C. for 25 min to 35 min to obtain a primary gel.
[0067] S60, after introducing disulfide bonds into the primary gel, performing cross-linking strengthening and sterilization to obtain a silk fibroin composite gel.
[0068] Specifically, the primary gel is immersed in a PBS buffer containing cystamine, the pH is adjusted to 7.0-7.5, cross-linked at 35°C-40°C for 2h-4h to form a dynamic disulfide bond network, and then sterilized with γ rays at a dose of 15kGy-25kGy to obtain a silk fibroin composite gel.
[0069] This application first forms an injectable primary gel through mild Schiff base bonds, and then enhances the long-term stability of the composite gel through disulfide bond post-crosslinking. The Schiff base bonds (high dynamics but low strength) and disulfide bonds (high strength and controllable degradation) work together to enable the composite gel to maintain injectability and improve mechanical strength through disulfide bond post-crosslinking after implantation, so that the composite gel can be reshaped after injection to match complex tissue morphology and have strong self-repair ability.
[0070] The embodiments of the present application also provide a silk fibroin composite gel, which is obtained using the above-mentioned method for preparing the silk fibroin composite gel.
[0071] The above technical solutions of the present application are described in detail below with reference to specific embodiments.
[0072] Example 1
[0073] A method for preparing a silk fibroin composite gel comprises the following steps:
[0074] 1. Preparation of silk fibroin solution
[0075] Silk fibroin was dissolved in a 9.3 mol / L LiBr solution at a solid-to-liquid ratio of 1:10, stirred and dissolved at 60°C for 2 h, injected into a dialysis bag with a molecular weight cutoff of 12 kDa, and dialyzed in deionized water for 72 h (with the water changed every 4 h) until the conductivity was <5 μS / cm. The solution was then rotary evaporated at 40°C to a mass fraction of 8% and stored at 4°C until further use.
[0076] 2. Preparation of Aminated Silk Fibroin
[0077] To 50 mL of silk fibroin solution, add 1,2-ethylenediamine (the molar ratio of silk fibroin to 1,2-ethylenediamine is 1:6), 50 mM EDC, and 60 mM NHS. Adjust the pH to 6.5, and react with magnetic stirring at 25°C for 24 h. Then, inject into a dialysis bag with a molecular weight cutoff of 3.5 kDa and dialyze against acetate buffer at pH 5.0 for 48 h. After freeze-drying, the amino-modified silk fibroin is obtained as a white powder and stored in a sealed container at -20°C.
[0078] 3. Preparation of oxidized sodium alginate
[0079] Dissolve 5 g of sodium alginate in 500 mL of pH 4.2 acetate buffer, add sodium periodate (the molar ratio of sodium alginate to sodium periodate is 1:0.9), and react in the dark with stirring for 7 h. Then, add 10 mL of ethylene glycol to terminate the reaction, and dialyze the solution in a dialysis bag with a molecular weight cutoff of 7 kDa for 48 h to remove unreacted products. After freeze-drying, oxidized sodium alginate with an oxidation degree of 25% is obtained, which is then stored in a dry place at 4°C.
[0080] 4. Preparation of Thermosensitive-Dynamic Double Network Pregel Solution
[0081] 5wt% amino-modified silk fibroin and 4wt% oxidized sodium alginate were dissolved in PBS buffer at 4°C, the pH was adjusted to 7.0, 12U / mL horseradish peroxidase and 4mmol / L hydrogen peroxide were added, and the mixture was stirred at 25°C for 25 minutes to obtain a dynamic cross-linked network solution.
[0082] N-isopropylacrylamide monomer, N,N-methylenebisacrylamide and ammonium persulfate were dissolved in water and reacted at 55-65°C for 3.5-4.5 hours under nitrogen atmosphere to obtain poly (N-isopropylacrylamide) (PNIPAM) microgel with a particle size of 80 nm.
[0083] 18 wt% Pluronic F127 and 4 wt% PNIPAM microgel were added to the dynamic cross-linked network solution and homogenized at 1000 rpm for 10 min to obtain a thermosensitive-dynamic dual network pregel solution, which was temporarily stored at 4°C.
[0084] 5. Preparation of active ingredients
[0085] 8 g of silk fibroin powder was dissolved in 92 mL of deionized water and stirred at 4°C and 500 rpm for 2 h until completely dissolved to obtain an 8 wt% silk fibroin solution. Lyophilized VEGF powder was added to the silk fibroin solution at a ratio of 1:10 (w / w) and vortexed for 5 minutes to obtain an inner phase solution.
[0086] Dissolve 5 g of polycaprolactone (molecular weight 50 kDa) in 95 mL of chloroform and stir in a 40°C water bath for 30 min. Then add lyophilized IL-10 powder (mass ratio of polycaprolactone to IL-10 20:1) and disperse by ultrasonication at 200 W for 10 min to obtain the external phase solution.
[0087] A coaxial needle (inner diameter 0.4 mm, outer diameter 1.2 mm) was used, with an internal phase flow rate of 0.5 mL / min and an external phase flow rate of 2 mL / min set. The internal phase solution and the external phase solution were injected into the inner and outer channels of the coaxial needle, respectively, and then added dropwise to a 1% (w / v) polyvinyl alcohol aqueous solution at a speed of 500 rpm to form a W / O / W double emulsion. The solution was stirred for 4 h to evaporate the chloroform. After the shell layer solidified, the solution was centrifuged at 3000 rpm for 10 min. The microspheres were collected, washed three times with deionized water, and freeze-dried to obtain core-shell microspheres.
[0088] 10 mg of graphene oxide powder was added to 10 mL of PBS buffer (pH 7.4) and ultrasonicated (power 300 W, frequency 40 kHz) for 1 h to obtain a 1 mg / mL graphene oxide dispersion.
[0089] 1 mg of antimicrobial peptide LL-37 was dissolved in 1 mL of PBS buffer and slowly added dropwise to the graphene oxide dispersion (the mass ratio of graphene oxide to LL-37 was 1:1). After stirring for 12 h, the mixture was centrifuged at 12,000 rpm for 20 min to remove unbound LL-37. The precipitate was then washed three times with PBS buffer to obtain graphene oxide nanosheet-anchored antimicrobial peptide (GO / LL-37).
[0090] 2 mmol MnCl2·4H2O and 4 mmol 2-methylimidazole were dissolved in 20 mL methanol, mixed, and ultrasonicated for 10 min. The mixture was then transferred to a 50 mL polytetrafluoroethylene autoclave and reacted at 100°C for 12 h. The precipitate was collected by centrifugation, washed three times with methanol, and then dried in vacuo at 60°C to obtain Mn-MOF.
[0091] 6. Primary gel formation
[0092] The core-shell microspheres, GO / LL-37 and Mn-MOF were ultrasonically dispersed (ultrasonic power of 100 W, ultrasonic time of 5 min) in the thermosensitive-dynamic double network pregel solution to obtain a composite gel solution.
[0093] After the composite gel solution was injected into the silicone mold, it was incubated at 37°C for 30 min to obtain the primary gel;
[0094] 7. Post-crosslinking strengthening
[0095] The primary gel was immersed in PBS buffer containing 0.2 mol% cystamine, the pH was adjusted to 7.2, and cross-linked at 37°C for 3 hours to form a dynamic disulfide bond network. The gel was then sterilized by γ-ray irradiation at a dose of 20 kGy and aseptically packaged at 4°C to obtain a silk fibroin composite gel.
[0096] Example 2
[0097] Compared with Example 1, the adjustment parameters are:
[0098] Dynamic cross-linking time in step 4: 20 min;
[0099] The ratio of the thermosensitive components in step 4: Pluronic F127 20wt%, PNIPAM microgel 5%;
[0100] In step 5, VEGF freeze-dried powder was added to the silk fibroin solution at a mass ratio of 1:8, and the mass ratio of polycaprolactone to IL-10 was 15:1;
[0101] Post-crosslinking time in step 7: 4 h.
[0102] Comparative Example 1 Single dynamic network gel (without temperature-sensitive component)
[0103] Compared with Example 1, Pluronic F127 and PNIPAM microgel were not added in step 4, and the remaining steps were the same.
[0104] Comparative Example 2: No core-shell microspheres
[0105] Compared with Example 1, core-shell microspheres were not prepared in step 5, VEGF and IL-10 were directly ultrasonically dispersed in the thermosensitive-dynamic double network pregel solution in step 6, and the remaining steps were the same.
[0106] Comparative Example 3: No graphene oxide nanosheets
[0107] Compared with Example 1, the preparation of GO / LL-37 in step 5 was omitted, and in step 6, free LL-37 was directly ultrasonically dispersed in the thermosensitive-dynamic double network pregel solution, and the remaining steps were the same.
[0108] Comparative Example 4 Static covalent crosslinking (glutaraldehyde crosslinking)
[0109] Compared with Example 1, the preparation process of the dynamic cross-linked network solution in step 4 is replaced by glutaraldehyde cross-linking, that is:
[0110] 5w% amino-modified silk fibroin and 4wt% oxidized sodium alginate were dissolved in PBS buffer at 4°C, the pH was adjusted to 8.0, 1wt% glutaraldehyde was added, and the mixture was stirred at 25°C for 24h to allow the glutaraldehyde to fully react with the amino groups of the amino-modified silk fibroin to form covalent imine bonds; 0.1M glycine was then added to block the unreacted aldehyde groups and terminate the cross-linking reaction. The mixture was then injected into a dialysis bag with a molecular weight cutoff of 7kDa and dialyzed for 48h to remove residual glutaraldehyde to obtain a static covalent cross-linked network solution; the remaining steps were the same as in Example 1.
[0111] Comparative Example 5: No post-crosslinking strengthening with cystamine
[0112] Compared with Example 1, in step 7, the primary gel is not immersed in cystamine-containing PBS buffer, but is directly irradiated for sterilization. The remaining steps are the same.
[0113] Experimental Example 1
[0114] A TA Instruments DHR-3 rheometer was used with the following settings: plate-plate mode (20 mm diameter, 1 mm spacing), temperature sweep (25°C → 45°C, rate 2°C / min), frequency 1 Hz, strain 1%, to test the rheological properties of the composite gels in Example 1 and Comparative Examples 1-5. The test indicators included: 25°C viscosity, 37°C gelation time, elastic modulus (G'), 45°C modulus reversible adjustment rate, and self-repair rate (i.e., the ratio of the recovery modulus to the original value after shear failure). The test results are shown in Tables 1 and 2. Figure 2 shown.
[0115] Table 1
[0116]
[0117] From Table 1 and Figure 2It can be seen that the viscosity of the composite gel in Comparative Example 1 at 25°C is significantly higher than that in Example 1, and the gelation time at 37°C is >300s, while that in Example 1 is <10s, and the elastic modulus G' in Comparative Example 1 is only 0.2kPa, and the self-repair rate is 72%, indicating that the use of a single dynamic cross-linking network in Comparative Example 1 has a greater influence on the rheological properties of the composite gel, its injectability is poor, and the self-repair rate is also reduced; the composite gel in Comparative Example 4 has the highest viscosity at 25°C, and the gelation time at 37°C is >1800s, the modulus adjustment rate at 45°C is 0, and the self-repair rate is 0, indicating that the composite gel formed by static cross-linking of covalent imine bonds in Comparative Example 4 is completely irreversible, cannot trigger secondary shaping, and has poor injectability; in Comparative Example 5, no disulfide bond is introduced for post-crosslinking strengthening, resulting in a certain degree of decrease in the elastic modulus G', 45°C modulus adjustment rate and self-repair rate of the composite gel, indicating that cross-linking strengthening of disulfide bonds is beneficial to improving the mechanical strength of the composite gel. This shows that the thermosensitive-dynamic dual network in the embodiment of the present application is conducive to achieving rapid gelation, and the dynamic bonds support reversible shaping, and the disulfide bond reinforcement can provide mechanical support.
[0118] Experimental Example 2
[0119] The composite gels of Example 1 and Comparative Example 2 were immersed in PBS buffer at 37°C, pH 7.4, and samples were taken at regular intervals. The release of VEGF was detected by HPLC, and the release of IL-10 was detected by ELISA. The cumulative release rates of VEGF and IL-10 were calculated.
[0120] Wherein, cumulative release rate = release amount / total drug loading amount × 100%.
[0121] The test results are shown in Table 2 below.
[0122] Table 2
[0123] Group VEGF release rate (24h) VEGF release rate (28 days) IL-10 release rate (5 days) Example 1 8 75 85 Comparative Example 2 85 95 20
[0124] As shown in Table 2, after 24 hours, the composite gel in Comparative Example 2 released 85% of VEGF, while the composite gel in Example 1 released <10% of VEGF. Furthermore, after 28 days, the cumulative VEGF release rate in the composite gel in Example 1 was 75%, indicating incomplete release, while the VEGF in the composite gel in Comparative Example 2 was essentially depleted. After 5 days, the IL-10 release rate in the composite gel in Example 1 was 85%, while the IL-10 release rate in the composite gel in Comparative Example 2 was 20%. This indicates that the core-shell microspheres used in the present invention to encapsulate VEGF and IL-10 achieve a controlled release sequence (sustained VEGF release + immediate IL-10 release), allowing for angiogenesis and anti-inflammatory effects to be linked in an orderly manner, avoiding the release chaos and functional antagonism that occurs when VEGF and IL-10 are directly added in Comparative Example 2.
[0125] In summary, the amino-modified silk fibroin and oxidized sodium alginate are cross-linked through dynamic Schiff base bonds in this application to support reversible plasticity. F127 / PNIPAM microgel provides thermosensitive rapid gelation and adopts a staged cross-linking strategy, first rapidly forming through dynamic Schiff base bond cross-linking, and then strengthening through disulfide bonds to improve long-term stability. Before injection (at low temperature), the dynamic bonds (Schiff base bonds) of the composite gel of this application are in a weakly cross-linked state to maintain fluidity. After injection into the body, the dynamic bonds are triggered to reorganize by body temperature (37°C), and it can quickly solidify to form a gel, which not only maintains injectability but also improves mechanical strength through disulfide bond post-cross-linking after implantation. After injection, it can be reshaped to match complex tissue morphology and has strong self-repair ability. This application adopts a core-shell microsphere gradient drug delivery system to release VEGF (long-acting angiogenic) and IL-10 (fast-acting anti-inflammatory) in a timely manner to avoid drug antagonism and enhance therapeutic synergy. At the same time, the antibacterial-antioxidant complex synergistically blocks the vicious cycle of "infection-inflammation-oxidative stress". This application systematically solves the problems of traditional injectable gels such as irreversibility, difficulty in matching complex tissue contours, single function, and easy collapse after filling through the integration of thermosensitive-dynamic dual network design, core-shell microsphere gradient drug loading and antibacterial-antioxidant complexes, and realizes the integration of "injection-gelation-shaping", which is suitable for soft tissue repair and medical aesthetic filling.
[0126] The above are merely optional embodiments of the present application and do not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification and drawings under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.
Claims
1. A method for preparing a silk fibroin composite gel, characterized in that: The following steps are involved: preparing silk fibroin and performing amino modification on it to obtain amino-modified silk fibroin; The amino-modified silk fibroin and oxidized sodium alginate are dynamically cross-linked via Schiff base bonds using an enzyme-catalyzed cross-linking process to obtain a dynamic cross-linked network solution; Adding a temperature-sensitive component to the dynamic cross-linked network solution and mixing them to obtain a temperature-responsive temperature-sensitive-dynamic double network pregel solution; loading active ingredients into the thermosensitive-dynamic double network pregel solution to obtain a composite gel solution; After incubating the composite gel solution, a primary gel is obtained; After disulfide bonds are introduced into the primary gel, cross-linking strengthening and sterilization are performed to obtain a silk fibroin composite gel.
2. The method for preparing the silk fibroin composite gel according to claim 1, wherein The step of preparing silk fibroin and performing amino modification on it to obtain amino-modified silk fibroin comprises: Dissolve silk fibroin in lithium bromide solution, stir and dissolve at 60-65°C for 1-2 hours, and then dialysis and purification, and concentrate to a mass fraction of 6%-8% to obtain a silk fibroin solution; 1,2-ethylenediamine is added to the silk fibroin solution, and then an EDC / NHS activator is added, and the pH is adjusted to 6.3-6.
7. After reacting for 22 hours to 26 hours, the solution is dialyzed and freeze-dried to obtain amino-modified silk fibroin.
3. The method for preparing the silk fibroin composite gel according to claim 1, wherein: The step of dynamically cross-linking the amino-modified silk fibroin and oxidized sodium alginate via Schiff base bonds using an enzyme-catalyzed cross-linking process to obtain a dynamic cross-linked network solution comprises: The amino-modified silk fibroin and oxidized sodium alginate are dissolved in a PBS buffer solution at 4° C. to 10° C., and horseradish peroxidase and hydrogen peroxide are added thereto, and the mixture is reacted for 20 min to 30 min to form a Schiff base cross-linking system, thereby obtaining a dynamic cross-linking network solution. The mass fraction of the amino-modified silk fibroin in the dynamic cross-linked network solution is 4wt%-6wt%; the oxidation degree of the oxidized sodium alginate is 20%-30%, and the mass fraction of the oxidized sodium alginate in the dynamic cross-linked network solution is 3wt%-5wt%.
4. The method for preparing the silk fibroin composite gel according to claim 1, wherein The temperature-sensitive component includes poloxamer F127 and poly (N-isopropylacrylamide) microgel.
5. The method for preparing the silk fibroin composite gel according to claim 1, wherein The step of loading the active ingredient into the thermosensitive-dynamic double network pre-gel solution to obtain a composite gel solution comprises: Ultrasonic dispersion of active ingredients in the thermosensitive-dynamic double network pre-gel solution to obtain a composite gel solution; The active ingredients include core-shell microspheres encapsulating growth factors and anti-inflammatory factors, antimicrobial peptides anchored by graphene oxide nanosheets, and superoxide dismutase mimics.
6. The method for preparing the silk fibroin composite gel according to claim 5, wherein: The core-shell microspheres are prepared by the following steps: Dissolve silk fibroin in water, add vascular endothelial growth factor freeze-dried powder, and vortex mix for 4-6 minutes to obtain the inner phase solution; Dissolve polycaprolactone in chloroform, stir in a water bath at 37-42°C for 25-35 minutes, then add interleukin-10 freeze-dried powder, and disperse by ultrasonication to obtain an external phase solution; The inner phase solution and the outer phase solution were added dropwise to a polyvinyl alcohol aqueous solution at a rotation speed of 450-550 rpm by a coaxial emulsification-solvent evaporation method to form a W / O / W double emulsion, which was then solidified and centrifuged to obtain the core-shell microspheres.
7. The method for preparing the silk fibroin composite gel according to claim 5, wherein: The graphene oxide nanosheet-anchored antimicrobial peptide is prepared by the following steps, including: Graphene oxide powder was added to PBS buffer and ultrasonically treated to obtain a graphene oxide dispersion. The antimicrobial peptide LL-37 was dissolved in PBS buffer, and then added dropwise to the graphene oxide dispersion. After stirring for 10 hours to 14 hours, the mixture was centrifuged at a rate of 11,000 rpm to 13,000 rpm for 15 minutes to 25 minutes. After washing, the graphene oxide nanosheet-anchored antimicrobial peptide was obtained.
8. The method for preparing the silk fibroin composite gel according to claim 5, wherein: The superoxide dismutase mimetic is a manganese-based metal organic framework, which has a porous structure formed by manganese ions and organic ligands and is grafted into the thermosensitive-dynamic double network pregel solution through covalent bonds.
9. The method for preparing the silk fibroin composite gel according to claim 1, wherein: The step of introducing disulfide bonds into the primary gel, performing cross-linking strengthening and sterilization to obtain a silk fibroin composite gel comprises: The primary gel is immersed in a PBS buffer containing cystamine, the pH is adjusted to 7.0-7.5, cross-linked at 35-40° C. for 2 h to 4 h to form a dynamic disulfide bond network, and then sterilized with γ rays at a dose of 15 kGy-25 kGy to obtain a silk fibroin composite gel.
10. A silk fibroin composite gel, characterized in that: The silk fibroin composite gel is obtained by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation, raw material, product and application of optical coupling synergistic cross-linked hydrogel material
CN112142870A
Sodium alginate and silk fibroin subject-object cross-linked hydrogel as well as preparation method and application thereof
CN117801322A
Aminated silk fibroin bridged dual-network sodium hyaluronate / silk fibroin gel and preparation method thereof
CN118085336A
High-modulus strong-adhesion injectable hydrogel as well as preparation method and application thereof
CN119367585A
Self-healing injectable photo-crosslinking dual-network hydrogel and preparation method thereof
CN119798715A
Cited By
Degradable sponge and preparation process thereof
CN120944197A
Composite porous microsphere capable of self-crosslinking when meeting blood and preparation method of composite porous microsphere
CN121401482A
Silk fibroin modified silica gel chromatographic filler as well as preparation method and application thereof
CN121695839A
Silk fibroin composite microsphere, gel, preparation method and application
CN122057079A
Composition for improving skin elasticity and method for preparing the same
KR102979708B1